Witnessing You : On Trust and Truth in a Networked World - Nevejan, Caroline (Delft : Participatory Systems Initiative, Delft University of Technology, 2012)
van Lohuizen, Kadir ; Solomon, Debra ; Ophuis, Ronald ; Feigl, Zoro ; de Jong, Afaina ; Chen, Chin-Lien, Vermaas, Chris ; Carlgren, Anna ; Twaalfhoven, Merlijn ; Butler, Martin ; Lancel, Karen ; Maat, Hermen ; Jodi ; Maurer, Luna ; Zangger, Andreas ; Vermeulen, Angelo
boek